Multidrug resistance in stray cats of the North Surabaya Region, East Java, Indonesia - Wibisono, F.J.; Widiasih, D.A.; Mentari, A.O.; Isnaeni, M.; Qurratu'ain, S.H.; Jalal, I.; Islam, A.F.; Fardiansyah, A.; Hung Nguyen-Viet (Science-line Publishers, 2024)
Stray cats survive by getting food or drink that is available in the environment, correspondingly, stray cats have relatively high exposure to antibiotic resistance obtained from resistant bacteria found in the environment. The present study was conducted to determine patterns of multidrug resistance and Escherichia coli resistance in stray cats. A total of 50 stray cat anal swab samples were taken randomly from the previously recorded stray cat population in the Surabaya area, East Java, Indonesia. Samples were brought using buffered peptone water. They were cultured on MacConkay Agar differential selective media, and all suspicious colonies of Escherichia coli were examined by biochemical tests. Isolates were then identified, and susceptibility testing was performed according to the Clinical and Laboratory Standards Institute. The results of the resistance test indicated that the multidrug resistance in Escherichia coli bacteria taken from cats was 14.6% (7/48). The high antibiotic resistance of Escherichia coli bacteria in stray cats, which were resistant to many drugs, provides an early warning of environmental health. Environmental health is closely related to animal and human health, especially antibiotic resistance.